Glucotropaeolin Promotes Apoptosis by Calcium Dysregulation and Attenuates Cell Migration with FOXM1 Suppression in Pancreatic Cancer Cells - Woonghee Lee; Gwonhwa Song; Hyocheol Bae (MDPI AG, 2023)
Pancreatic ductal adenocarcinoma (PDAC) has naturally aggressive characteristics including postoperative recurrence, resistance to conventional treatment, and metastasis. Surgical resection with chemotherapeutic agents has been conducted as the major treatment for PDAC. However, surgical treatment is ineffective in the case of advanced cancer, and conventional adjuvant chemotherapy, including gemcitabine and 5-fluorouracil, show low effectiveness due to the high drug resistance of PDAC to this type of treatment. Therefore, the development of innovative therapeutic drugs is crucial to solving the present limitation of conventional drugs. Glucotropaeolin (GT) is a glucosinolate that can be isolated from the Brassicaceae family. GT has exhibited a growth-inhibitory effect against liver and colon cancer cells; however, there is no study regarding the anticancer effect of GT on PDAC. In our study, we determined the antiproliferative effect of GT in PANC-1 and MIA PaCa-2, representative of PDAC. We revealed the intracellular mechanisms underlying the anticancer effect of GT with respect to cell viability, reactive oxygen species (ROS) accumulation, alteration of mitochondrial membrane potential (MMP), calcium dysregulation, cell migration, and the induction of apoptosis. Moreover, GT regulated the signaling pathways related to anticancer in PDAC cells. Finally, the silencing of the forkhead box protein M, a key factor regulating PDAC progression, contributes to the anticancer property of GT in terms of the induction of apoptosis and cell migration. Therefore, GT may be a potential therapeutic drug against PDAC.